Citation Analysis of Published Scientific Production References by Faculty Members of Tonekabon Branch Islamic Azad University At ISI, ISC, and Scopus databases - Seyed rasool Toudar (Institute of Management fekrenoandish, 2019)
This study investigates the articles published by the faculty members of Islamic Azad University of Tonekabon in authentic scientific sources at ISI, ISC, and Scopus databases. This is an applied research and has been carried out by book-assessment style, using the citation analysis method. The findings of this study showed a total of 7166  citations by the group in three bases, of which 3917 (55%) to basic science, 860 (12%) to humanities and social sciences 2333 (33%) and There were 57 cases (0.8%). Most citations (88.7%) were in the form of articles. The research hypothesis that faculty members of Tonekabon Azad University cite more scientific journals in journal articles proves the highest percentage of citations among faculty members' tendencies to basic science researchers with 55% and the lowest percentage of citations to physicians, and humanities and engineering sciences with citation rates of 33% and 12%, respectively. In terms of language, English sources were more widely cited than sources in other languages. The number of citations to printed / electronic sources in faculty articles of all colleges was very high. And the research hypothesis that faculty members at Tonekabon Azad University in writing of scientific papers rely more on printed sources than on non-printed sources rejects and does not approve it. And the low percentage of citations to theses thesis hypothesis confirms little contribution to the research papers of the researched university.